System change in practice: A report from the EHC Think Tank workstreams on Registries and Patient Agency - Gacser Zita; Skouw-Rasmussen Naja (The Journal of Haemophilia Practice)
System change addresses the fundamental causes of persistent, complex problems to achieve large-scale, sustainable solutions at multiple levels. Recognising the need for system change to ensure equitable access to healthcare for people with bleeding disorders and other rare diseases, the European Haemophilia Consortium (EHC) established a Think Tank to work alongside its traditional advocacy initiatives. The Think Tank has mobilised a broad range of healthcare stakeholders to identify challenges and co-create potential solutions through a series of thematic workstreams exploring specific aspects of the healthcare system. This paper reports on outcomes and learnings from the Registries and Patient Agency workstreams.